Fatty Acid Profile and Some Useful Biological Aspects of Borage, Calophyllum, and Prickly Pear Seed Oils: Implications for Health and Dietary Use - Florinda Fratianni; Francesca Coppola; Siria Tavaniello; Maria Neve Ombra; Beatrice De Giulio; Nunzio D’Agostino; Gokhan Zengin; Raffaele Coppola; Filomena Nazzaro (Antioxidants)
Seed oils from Borago officinalis (borage), Opuntia ficus-indica (prickly pear), and Calophyllum inophyllum (calophyllum or tamanu) are rich in bioactive fatty acids and have been traditionally used in cosmetic and industrial sectors. This study explored their fatty acid composition and investigated their in vitro antioxidant, anti-arthritic, neuroprotective, and antibiofilm activities. Fatty acid profiles were determined via gas chromatography. Antioxidant activity was assessed using DPPH and ABTS radical scavenging assays. Anti-arthritic potential was measured via bovine serum albumin denaturation. Neuroprotective properties were evaluated through acetylcholinesterase, butirylcholinesterase, and tyrosinase inhibition. Antibiofilm activity against five pathogenic strains was analyzed using crystal violet and MTT assays. Correlation analysis was used to associate fatty acid composition with bioactivity. Prickly pear oil exhibited the highest PUFA content (65.1%), mainly linoleic acid. Calophyllum oil was richer in saturated and monounsaturated fatty acids. All oils showed significant radical scavenging ability, with calophyllum oil showing the lowest DPPH IC50 and borage oil, the highest ABTS activity. Borage and prickly pear oils demonstrated strong anti-arthritic potential. Calophyllum oil showed the most potent AChE inhibition. All oils showed tyrosinase inhibition; however, calophyllum did not show BChE inhibitory activity. Antibiofilm activity was species- and dose-dependent, with Staphylococcus aureus, Escherichia coli, and Acinetobacter baumannii being most affected. Thus, the tested oils exhibited multiple biological activities, influenced by their fatty acid composition. The in vitro antioxidant, anti-arthritic, neuroprotective, and antimicrobial properties support their potential use as functional food ingredients or nutraceuticals, especially for aging-related health concerns. Further in vivo and clinical studies are needed to confirm their efficacy.